Use of Dendrimers during the Synthesis of Pt-Ru Electrocatalysts for PEM Fuel Cells: Effects on the Physical and Electrochemical Properties. (4th August 2011) - Calderón, J. C.; Calvillo, L.; Lázaro, M. J.; Pastor, E.
Abstract : In this work, Pt-Ru catalysts were synthesized by a novel methodology which includes the use as encapsulating molecules of dendrimers of different generation: zero (DN-0), one (DN-1), two (DN-2), and three (DN-3). Synthesized catalysts were heat-treated at 350°C, and the effects of this treatment was established from the physical (X-ray dispersive energy (XDE) and X-ray diffraction (XRD)) and electrochemical characterization (cyclic voltammetry and chronoamperometry). Results showed that the heat-treatment benefits the catalytic properties of synthesized materials in terms of CO and methanol electrochemical oxidation. The curves for CO stripping were more defined for heat-treated catalysts, and methanol oxidation current densities were higher for these materials. These changes are principally explained from the removal of organic residues remaining on the surface of the Pt-Ru nanoparticles after the synthesis procedure. After the activation of the catalysts by heating at 350°C, the real importance of the use of these encapsulating molecules and the effect of the generation of the dendrimer become visible. From these results, it can be concluded that synthesized catalysts are good catalytic anodes for direct methanol fuel cells (DMFCs).